Serum FT3/FT4, but not TSH is associated with handgrip strength in euthyroid U.S. population: evidence from NHANES - Wang, Zhizhuo; Wu, Peiyun; Yang, Jing; Jiang, Yuanshan; Wang, Juan; Lin, Cheng (Frontiers in Endocrinology, 2024)
Objective: Although several studies have examined the relationship between thyroid function and muscle strength, their population primarily derived from Asian areas, and their results were controversial. Thus, this study aimed to explore the association between thyroid function and handgrip strength (HGS) in the U.S. population.Methods: A total of 1,067 participants from NHANES were categorized into three different age groups including young (<45 years), middle (45~64 years), and old (≥65 years) age groups. Thyroid function was measured by the competitive binding immune-enzymatic assays, while HGS was examined by a trained evaluator using a dynamometer. The weighted multiple linear regression models were used to examine the association between thyroid function and handgrip strength. The restricted cubic splines were employed to explore the non-linear relationship between these two variables. All statistical analyses were performed using the SPSS version 20.0 and R software.Results: After adjustment for potential covariates, FT3/FT4, but not TSH was positively associated with HGS in middle age group (β=0.091, t=2.428, P=0.016). The subgroup analysis by sex revealed that the positive association between FT3/FT4 and HGS was observed in the middle age group for both male and female participants (β=0. 163, t=2.121, P=0.035; β=0.157, t=2.180, P=0.031). The RCS analysis showed a statistically significant non-linear association between FT3/FT4 and HGS in overall population (P for non-linear=0.026). After adjustment for covariates, men with low HGS had a significant lower FT3/FT4 than those without low HGS in old age group (P=0.013). There was a significant increase in TSH level for female participants with low HGS in old age group compared to those with normal HGS (P=0.048).This study demonstrated FT3/FT4, but not TSH, was positively associated with HGS in middle age group, and the different association was observed in men in middle age group when participants were stratified by sex. Future longitudinal cohort study should be conducted to reveal the causal relationship between thyroid function and muscle strength.